A Bird and schoolchildren: Knowledge sharing about Kenyalang (Rhinoceros Hornbill) by schoolchildren in Sarawak via social media - Justin Dit, Terry; Flenny Gawin, Dr Dency (2021)
Kenyalang, also known as Rhinoceros Hornbill in English and Enggang Badak in Bahasa Melayu, is the state bird of Sarawak. However, many Malaysians including Sarawakians are confused between Kenyalang and other hornbill species. Therefore, this study observes how knowledge sharing via social media by schoolchildren can educate the communities to know about Kenyalang. Students, teachers from five schools as well as parents were involved in creating a short video about Kenyalang. The video was uploaded into the the Kenyalang Lab YouTube Channel, and made it public for many people to watch, learn and share using other social media platforms. Data such as number of views, likes, shares as well as comments were collected within one week. Selected respondents were interviewed virtually via Zoom, or the respondents recorded their interviewed videos and sent via Telegram, WhatsApp and e-mail. The video received good responses from viewers, teachers, students and parents. It is also suitable for public whom want to know more about Kenyalang. By continuously adding informative and interesting videos, the Kenyalang YouTube Channel can be accepted as an educational channel for locals and people outside of Sarawak who want to know more about birds of Sarawak.